(untitled) (LACCEI, 2024)
Seismic site analysis is an important step on the design of both conventional structures as well as critical infrastructure, such as water supply pipelines, sewers and roads. This article present results of an experimental investigation that used the geophysical method refraction microtremor (ReMi) for determination of shear wave velocities in soil of Boquete City, Republic fo Panama. As part of this research, a field exploration campaign was developed on which ReMi studies were carried out on six points along the David – Boquete Road. Results show that there are different stratigraphic profiles for Bajo and Alto Boquete zones, which is shown by the shear wave profiles obtained. Results of the study herein presented are fundamental in order to be able to develop seismic site characterization, which is at the same time useful for infrastructure design.